2000
DOI: 10.1136/ard.59.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Impaired microvascular response to cholinergic stimuli in primary Sjogren's syndrome

Abstract: Unresponsiveness to cholinergic stimuli may contribute to exocrine insuYciency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 20 publications
2
24
0
4
Order By: Relevance
“…In the SS-I patients, the chronic presence of inflammation caused by the lymphocytic infiltration of the lachrymal gland reduces tear secretion and corneal sensitivity, 31 as also found by others 32 and supported by morphological findings. 33 A reduced tear secretion, consequent to reduced corneal sensitivity, could also be in relation with an impairment in the parasympathetic control of lachrymal gland, as demonstrated in other exocrine gland, 34,35 as a consequence of the presence of anti M3 muscarinic receptors 36 independently from the concurrent presence of anti-SSA and anti-SSB, 37 as it has been demonstrated in an animal model. 38 A reduced tear clearance rate results in accumulation of corneal metabolism products, including the inflammatory cytokines present in the tear fluid of SS-I patients 39,40 maintaining the ocular surface inflammation within a vicious circle.…”
Section: Eyementioning
confidence: 90%
“…In the SS-I patients, the chronic presence of inflammation caused by the lymphocytic infiltration of the lachrymal gland reduces tear secretion and corneal sensitivity, 31 as also found by others 32 and supported by morphological findings. 33 A reduced tear secretion, consequent to reduced corneal sensitivity, could also be in relation with an impairment in the parasympathetic control of lachrymal gland, as demonstrated in other exocrine gland, 34,35 as a consequence of the presence of anti M3 muscarinic receptors 36 independently from the concurrent presence of anti-SSA and anti-SSB, 37 as it has been demonstrated in an animal model. 38 A reduced tear clearance rate results in accumulation of corneal metabolism products, including the inflammatory cytokines present in the tear fluid of SS-I patients 39,40 maintaining the ocular surface inflammation within a vicious circle.…”
Section: Eyementioning
confidence: 90%
“…Salivary secretion by salivary acinar cells follows cholinergic stimulation of muscarinic type 3 receptors (M 3 R) (1)(2)(3). Recent data have suggested that putative antibodies directed against M 3 R (anti-M 3 R), present in the IgG serum fraction of patients with primary SS, may contribute to the hypofunction of the salivary glands (4)(5)(6)(7)(8) and be responsible for a host of extraglandular features, such as bladder (9,10) and colon (11) irritability, Adie tonic pupil (12), and altered microvascular responses (13).…”
Section: ؉mentioning
confidence: 99%
“…In SS patients, isolated salivary acinar cells remain functional in vitro [92,93], but with a reduced sensitivity to threshold levels of muscarinic stimulation [93], suggesting that the lack of glandular function in many patients with SS is the result of a perturbation of acinar function [94,95]. In addition, perturbation of muscarinic receptor function by the presence of antimuscarinic antibodies would account, in large part, for some of the reported extraglandular features of SS, such as bladder irritability [90,96,97], impairment of esophageal motor function [98], and microvascular responses to cholinergic stimulation [99], Adie pupil [100], and variable heart rate [101]. In one study, the antibody levels against the 213-228aa peptide of M3R correlated positively with the number of extraglandular organ manifestations [87].…”
Section: Autoantibodies Associated With Particular Disease Manifestatmentioning
confidence: 99%